Antiviral efficacy of nanomaterial-treated textiles in real-life like exposure conditions - Nefedova, Alexandra; Rausalu, Kai; Zusinaite, Eva; Kisand, Vambola; Kook, Mati; Smits, Krisjanis; Vanetsev, Alexander; Ivask, Angela (Elsevier, 2023)
Due to the growing interest towards reducing the number of potentially infectious agents on critical high-touch surfaces, the popularity of antimicrobially and antivirally active surfaces, including textiles, has increased. The goal of this study was to create antiviral textiles by spray-depositing three different nanomaterials, two types of CeO2 nanoparticles and quaternary ammonium surfactant CTAB loaded SiO2 nanocontainers, onto the surface of a knitted polyester textile and assess their antiviral activity against two coronaviruses, porcine transmissible gastroenteritis virus (TGEV) and severe acute respiratory syndrome virus (SARS CoV-2). Antiviral testing was carried out in small droplets in semi-dry conditions and in the presence of organic soiling, to mimic aerosol deposition of viruses onto the textiles. In such conditions, SARS CoV-2 stayed infectious at least for 24 h and TGEV infected cells even after 72h of semi-dry deposition suggesting that textiles exhibiting sufficient antiviral activity before or at 24 h, can be considered promising. The antiviral efficacy of nanomaterial-deposited textiles was compared with the activity of the same nanomaterials in colloidal form and with positive control textiles loaded with copper nitrate and CTAB. Our results indicated that after deposition onto the textile, CeO2 nanoparticles lost most of their antiviral activity, but antiviral efficacy of CTAB-loaded SiO2 nanocontainers was retained also after deposition. Copper nitrate deposited textile that was used as a positive control, showed relatively high antiviral activity as expected. However, as copper was effectively washed away from the textile already during 1 h, the use of copper for creating antiviral textiles would be impractical. In summary, our results indicated that antiviral activity of textiles cannot be predicted from antiviral efficacy of the deposited compounds in colloid and attention should be paid on prolonged efficacy of antivirally coated textiles.--//-- Alexandra Nefedova, Kai Rausalu, Eva Zusinaite, Vambola Kisand, Mati Kook, Krisjanis Smits, Alexander Vanetsev, Angela Ivask, Antiviral efficacy of nanomaterial-treated textiles in real-life like exposure conditions, Heliyon, Volume 9, Issue 9, 2023, e20067, ISSN 2405-8440, https://doi.org/10.1016/j.heliyon.2023.e20067. Published under the CC BY-NC-ND licence.
We thank the following people and institutions for their contribution to our investigation. Toomas Varjund from TAD Logistics OÜ for providing the textiles. Ülis Sõukand from Estonian Environmental Research Center for his help with methods of chemical analysis. Estonian Research Council projects COVSG2, PRG629, PRG1496, PRG1154 and European Commission project STOP (Grant agreement ID: 101057961) for their financial support. The Center of nanomaterials technologies and research (NAMUR+) for core facility funded by project TT13 which was used conducting the research.
Keywords: Polyester fabric; Nanoparticles; Silicon dioxide; Cerium dioxide; Hexadecyltrimethylammonium bromide; Copper nitrate; Coronavirus; SARS-CoV-2; Antiviral; Virucidal